HUBUNGAN ASUPAN PANGAN PROTEIN BALITA DENGAN STUNTING DI DESA LOKASI FOKUS (LOKUS) STUNTING KABUPATEN BUNGO PROVINSI JAMBI TAHUN 2022 - Silvia Mawarti Perdana; Vika Aprianoza; Puspita Sari (Jurnal Mitra Kesehatan, 2023)
Objective:Thie research aimed to analyze the correlation of animal and vegetable protein’s intake and the irevalence of stunting in the stunting locus village, Bungo Regency, Jambi Province. Method: This study used cross sectional design on 88 respondents. The sampling technique used proportional simple random sampling. The instruments in this study were microtoise and food recall form. Data analysis used univariate and bivariate analysis (chi-square test). Results: The results of this study showed that there was no significant relationship between animal and vegetable protein intake and the incidence of stunting, because it was based on the results of the Chi Square Test animal protein (p-value 1.000) and vegetable protein (p-value 0.631). This means that intake of animal and vegetable protein is not affect the incidence of stunting. Conclusion: there is no significant relationship between intake of animal and vegetable protein and the incidence of stunting because it’s influenced by several factors, such as internal factors (age, physical condition and disease infection) and external factors (income, education, employment, culture, food intake).